The Influence of Auditor Independence, Auditor Competence, and Task Complexity on Audit Judgments at Food & Beverage Companies Period 2016 - 2020 - Adipraja, Martino Arogya (Budapest International Research and Critics University, 2021)
This study aims to determine the influence of auditor independence, auditor competence, and task complexity on audit judgments at food & beverage companies period 2016 - 2020. The analytical method used in this study is multiple Lnear Regression analysis using SPSS software. The results in this study are auditor independence, auditor competence, and task complexity has a positive effect on audit judgment.